A new interministerial strategy for the promotion of healthy eating in Portugal - Graça, Pedro (2018)
OBJECTIVE: To describe the implementation, main intervention areas and initial results of the Integrated Strategy for the Promotion of Healthy Eating (EIPAS) in Portugal. METHODS: EIPAS was published as a Law, in December of 2017, as a result of a collaboration between several ministries, including the Finance, Internal Affairs, Education, Health, Economy, Agriculture, and Sea Ministries, aiming at improving the dietary habits of the Portuguese population. The working group, led by the Ministry of Health, developed this strategy for over a year. The framework produced was based on WHO and European Commission recommendations as well as on relevant data from the last Portuguese dietary intake survey (2015/2016). EIPAS also reflects the results of a public hearing, including the food industry, among others, and the experience gathered, since 2012, through the National Programme for the Promotion of Healthy Eating. It considers the 'health in all policies' challenge set by WHO and has four different strategic areas, namely (1) creation of healthier food environments, (2) improvement of the quality and accessibility of healthy food choices for consumers, (3) promotion and development of literacy, in order to encourage healthy food choices, and (4) promotion of innovation and entrepreneurship. In order to achieve these goals, a set of 51 actions was established and assigned to the seven ministries involved. RESULTS: Under the scope of this strategy, Portugal has already implemented several actions, including (1) definition of standards for food availability at all public healthcare institutions; (2) implementation of a sugar tax on sweetened beverages; (3) implementation of a voluntary agreement with the food industry sector for food reformulation (work in progress); (4) design of a proposal for an interpretative model of front-of-pack food labelling; (5) improvement of the nutritional quality of food aid programmes for low-income groups; and (6) regulation of marketing of unhealthy foods to children. CONCLUSIONS: For the first time, Portugal has a nutrition policy based on the WHO concept of 'health in all policies' and on the national data on food intake. The implementing process of all 51 actions and the inherent complexities and difficulties found so far have made this process be an authentic political and social laboratory that deserves to be followed.